Contribution of land use changes to meteorological parameters in Greater Jakarta: Case 17 January 2014. (May 2018) - Nuryanto, D E; Pawitan, H; Hidayat, R; Aldrian, E
Abstract: The impact of land use changes on meteorological parameters during a heavy rainfall event on 17 January 2014 in Greater Jakarta (GJ) was examined using the Weather Research and Forecasting (WRF) model. This study performed two experimental simulation methods. The first WRF simulation uses default land use (CTL). The second simulation applies the experiment by changing the size of urban and built-up land use (SCE). The Global Forecast System (GFS) data is applied to provide more realistic initial and boundary conditions for the nested model domains (3 km, 1 km). The simulations were initiated at 00:00 UTC January 13, 2014 and the period of modeling was equal to six days. The air temperature and the precipitation pattern in GJ shows a good agreement between the observed and simulated data. The results show a consistent significant contribution of urban development and accompany land use changes in air temperature and precipitation. According to the model simulation, urban and built-up land contributed about 6% of heavy rainfall and about 0.2 degrees of air temperatures in the morning. Simulations indicate that new urban developments led to an intensification and expansion of the rain area. The results can support the decision-making of flooding and watershed management.